HUBUNGAN ANTARA KOMPETENSI DAN PENERAPAN SISTEM MANAJEMEN MUTU DENGAN KEPUASAN KERJA KARYAWAN - Supriyatno, Supriyatno (Jurnal Ekonomi, 2016)
This research was conducted to analyze the Competency and System Applied Quality Management ISO 9001: 2000 about Employee Satisfaction Work in Mercu Buana University at Jakarta. A survey method used during this research in which questionnaires were distributed to the respondents. The hypothesis analysis used the technique of simple and multiple regression and followed by the correlation. Using  the Computer Program of SPSS (Statistical Product Service and Solution) with n = 103 (respondents) and r-tabel = 0,195, the result showed that there was a less influenced  between Competency and System Applied Quality Management ISO 9001 : 2000  to  the Employee Satisfaction Work either Independent or concurrently. The Determinant Coefficients or Competency and System Applied Quality Management ISO 9001 : 2000  about Employee Satisfaction Work were  0,250 and  0,348. Which  means the  effects  of  Competency and System Applied Quality Management ISO 9001 : 2000 about  Employee Satisfaction  Work were  25 % and 34,8 % and the largely  influenced  by the factors. The Determinant Coefficients of Competency and System Applied Quality Management ISO 9001: 2000  about Employee Satisfaction Work was 0,420.  Which  means the effects of Competency and System Applied Quality Management ISO 9001: 2000 concurrently about Employee Satisfaction Work was 42% and the 58% Influenced  by other factors.